PENGARUH DEBT TO ASSET RATIO (DAR), DEBT TO EQUITY RATIO (DER), LONG TERM DEBT TO ASSET RATIO (LDAR) DAN LONG TERM DEBT TO EQUITY RATIO (LDER) TERHADAP PROFITABILITY (ROE) PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE 2012-2014 - Slamet Priyanto; Akhmad Darmawan (Media Ekonomi, 2017)
Every company in running their business has the goal to maximize the profit to enrich the owner or stock holder one of them is trough financing (modal structure). The decision in financing (modal structure) is an important aspect in getting maximal profit. This research aims to find out the effect of modal structure consisting : Debt To Asset Ratio (DAR), Debt To Equity Ratio (DER), Long Term Debt To Asset Ratio (LDAR), Long Term Debt To Equity Ratio (LDER) on Profitability (ROE) of the manufacture companies listed in Indonesia stock exchange (BEI) in the period of 2012-2014. This is a quantitative research. The population of this research is 141 manufacture companies listed in Indonesia Stock exchange. The sampling method was by purposive sampling. Based on determined criteria, there were 97 companies in a year therefore the total sample in 3 years was 291 samples. The research methodology was descriptive statistic analysis; statistic analysis was trough multiple linear regression and classical assumption test. The hypothesis test was by seeing the value of F count and t count in regression test. The result of the research showed that the coefficient of t test regression (partial) of DAR variable and LDER affected positively towards ROE, DER variable and LDAR negatively towards ROE. F test (simultaneously) of DAR, DER, LDAR & LDER affected positively towards ROE. Key words : Debt To Asset Ratio (DAR), Debt To Equity Ratio (DER), Long Term Debt To Asset Ratio (LDAR), Long Term Debt To Equity Ratio (LDER) and Profitability (ROE).